The influence of public policy on LGBT human rights in Indonesia: An analysis of literature study - Oktarina, Amalia Eka (Maliki Interdisciplinary Journal, 2024)
LGBT (Lesbian, Gay, Bisexual and Transgender) human rights are a hot topic in various countries, including Indonesia. This research aims to analyze the influence of public policy on LGBT human rights in Indonesia through a literature study approach. Through collecting and analyzing relevant literature, this research identifies the meaning of LGBT, policies related to LGBT, the legal basis for LGBT, and debates related to LGBT. This research explains that the treatment and views of society and the government can be influenced by public policy. Along with political and social dynamics in Indonesia, policies to recognize and protect the existence of LGBT are increasingly difficult to implement. This is due to cultural and religious factors. This analysis seeks to provide insight into how public policy influences efforts to protect LGBT human rights in Indonesia.